Research on stress intensity factors of elliptical hole in infinite body - Baoliang Liu; Guangping Zou (Functional Materials, 2016)
This paper deals with such a kind of surface crack problem with an approximately same depth by using the hybrid displacement discontinuity method (a boundary element method) proposed recently by the author. Based on surface rectangular crack in infinite solid in tension and a hybrid displacement discontinuity method, a numerical approach is presented. By changing geometry parameters of elliptical hole, the effect of geometry parameters of the elliptical hole in infinite body in tension on the SIFs is revealed in detail. It is illustrated that the boundary element method is simple, yet accurate for calculating the SIFs of complex crack problems in finite plate.